Venous and arterial thromboembolism in patients with cancer treated with targeted anti-cancer therapies. Issue 213 (May 2022) - Moik, Florian; Ay, Cihan
Abstract: Patients with cancer have an increased risk of venous- and arterial thromboembolism (VTE/ATE). Anti-cancer treatments including surgery, radiotherapy, and certain chemotherapies contribute to the increased risk of VTE and/or ATE. Over the past years, the therapeutic landscape in medical oncology has changed dramatically with the introduction of targeted anti-cancer therapies and cancer immunotherapy. These novel treatment approaches have revolutionized patient care with significant improvements in response rates and survival times of patients. These agents specifically target refined pathophysiological pathways engaged in tumour development and progression involving, among others, angiogenesis, growth factor receptor signalling and anti-tumoral immune regulation. Therefore, distinct off-target effects lead to characteristic adverse event profiles for certain treatments. For several targeted and immunotherapeutic anticancer agents, increased rates of VTE and/or ATE have been reported. For example, a prothrombotic effect has been reported for antiangiogenic agents, EGFR-targeted treatments, CDK4/6-inhibitors, and 2nd generation BCR-ABL-inhibitors. Further, very recently, data emerged on substantial rates of thrombotic complications in patients treated with immune checkpoint inhibitors. In this review, we comprehensively summarize currently available evidence on risk profiles and potential mechanisms of thrombosis in patients with cancer treated with targeted anti-cancer therapies, and discuss current limitations in available data and potential future perspectives. Highlights: Patients with cancer have an increased risk of venous and arterial thromboembolism. Increased thrombosis risk was reported for several targeted anti-cancer therapies. Emerging anti-cancer agents need specific evaluation of their prothrombotic potential. Novel risk-prediction tools for thrombosis in new anti-cancer therapies are needed.